Perilipin2-dependent lipid droplets accumulation promotes metastasis of oral squamous cell carcinoma via epithelial-mesenchymal transition - Jiayu Zhang; Jianmin Peng; Siyu Wang; Li Wang; Yutong Sun; Juan Xia; Bin Cheng; Qinchao Hu (Cell Death Discovery)
Abstract Emerging evidence shows that lipid metabolic reprogramming plays a vital role in tumor metastasis. The effect and mechanism of fatty acids and lipid droplets (LDs), the core products of lipid metabolism, on the metastasis of oral squamous cell carcinoma (OSCC), need further exploration. In this study, the influence of palmitic acid (PA) and oleic acid (OA) on the migration and invasion ability of OSCC cells was determined by in vitro experiments. Genetic manipulation of PLIN2 was performed to explore its effect on the accumulation of LDs and OSCC metastasis. Possible mechanisms of these biological effects were clarified by detecting the levels of epithelial-mesenchymal transition (EMT) markers and phosphatidylinositol 3-kinase (PI3K) pathway proteins as well as conducting various bioinformatics analyses. The results indicated that PA/OA promoted the migration and invasion of OSCC cells and induced PLIN2-dependent LDs accumulation in vitro. Knockdown of PLIN2 inhibited the LDs accumulation and the migration and invasion of OSCC cells in vitro, while overexpression of PLIN2 enhanced those of OSCC cells in vitro and also promoted the metastasis of OSCC in vivo. Besides, PLIN2 up-regulation activated the PI3K pathway and subsequently enhanced EMT in OSCC cells in vitro. OSCC patients with higher PLIN2 expression possessed poorer prognosis and higher sensitivity to chemotherapy drugs (1S,3 R)-RSL3 and ML-210. In conclusion, PLIN2-dependent LDs accumulation could promote the metastasis of OSCC cells by regulating EMT. PLIN2 might be a potential therapeutic target for OSCC patients, especially those with obesity.